Confinement effects of a crystalline sponge on ferrocene and ferrocene carboxaldehyde. Issue 41 (8th May 2017) - Brunet, Gabriel; Safin, Damir A.; Robeyns, Koen; Facey, Glenn A.; Korobkov, Ilia; Filinchuk, Yaroslav; Murugesu, Muralee
Abstract : The confinement effects of a crystalline sponge on organometallic sandwich compounds are investigated, in which a network of weak non-covalent interactions effectively dictate guest inclusion behaviour and motional dynamics. Abstract : The pivotal role of π⋯π interactions in the inclusion behaviour of a series of organometallic sandwich compounds is studied through single-crystal X-ray diffraction. The confinement effects of a crystalline sponge host are investigated where, notably, we observe an enhanced rotation of the ligand ring once encapsulated by the nanoporous framework, as evidenced by SSNMR experiments.